Nitrogen use efficiency in dry direct seeded rice under LCC based nitrogen management - Subedi, Purushottam; Sah, Shrawan Kumar; Marahattha, Santosh; Panta, Salina; Shrestha, Jiban (ORYZA-An International Journal of Rice, 2018)
The synchronization between crop demand and nitrogen supply is the most important aspect of increasing nitrogen (N) use efficiency, high yields and reduced nitrogen losses. Field experiment was conducted to evaluateleaf color chart (LCC) based nitrogen management on nitrogen use efficiency and productivity of dry direct seeded rice (DDSR) with five nitrogen management practices {0 kg N ha -1, 120 kg N ha-1in three split applications,30 kg N ha-1 as basal followed by 30 kg N ha-1 topdressing based on LCC critical value four, 30 kg N ha-1 topdressing (without basal N dose) at 15 days after sowing (DAS) followed by LCC based N application and pure LCC (without basal N dose) based N application} which were tested on three rice varieties (Radha-4, US- 312 and Sukkha-5) in split plot design. Pure LCC based N application had significantly higher agronomic efficiency (16 kg grain kg-1 N) and recovery efficiency (52 %) and partial factor productivity (43.56 kg grainkg-1 N) as compared to 120 kg ha-1 N in three split applications, 30 kg ha-1 N as basal followed by LCC based N application and 30 kg ha-1 N at 15 DAS followed by LCC based N application. Grain yield, NUEs (agronomic,recovery, partial factor productivity) and N uptake followed the trend; pure LCC > 30 kg N ha -1 at 15 DAS followed by LCC based N application > 30 kg N ha-1 as basal dose followed by LCC based N application > 120 kg N ha-1 applied in three splits